Characterization of ion tracks in CR39 polymer exposed to 241Am α-particles. Issue 9 (3rd October 2018) - Cannavò, A.; Lavrentiev, V.; Lavrentieva, I.; Torrisi, L.; Horàk, P.; Ceccio, G.; Vacìk, J.
ABSTRACT: The CR39 polymer (poly-allyl-diglycol carbonate) is considered as a valuable instrument to register various charged particles. In the current experiment, the CR39 material was tested whether it can identify and distinguish α -particles with different energy. For the purpose of the experiment, the CR39 foils were irradiated by α -particles from a thin 241 Am source; energy of the emitted α -particles was changed in the range from 3.5 to 5.5 MeV by varying the pressure in the vacuum chamber. The changes in the α -particles beam were monitored by a silicon detector and verified by SRIM simulations. The irradiated CR39 foils were etched in NaOH and analyzed by conventional optical microscopy (OM) and atomic force microscopy (AFM). The techniques were applied for analysis of the etched tracks – their outer diameters (OM and AFM) and depths (AFM). The combined application of these techniques allowed us to evaluate a clear correlation between the geometric parameters of the etched tracks and energy of the MeV α -particles, demonstrating that these techniques are a convenient tool for recognition of charged particles and certain identification of their energy.